Taxonomy of 'Euconnus complex'. Part XXIV. Intermediate forms between Psomophus, Eupentarius and Euconnus s. str. in the East Palaearctic fauna unify problematic subgenera (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2022)
Within the West Palaearctic region, the subgenera Psomophus and Eupentarius can be easily distinguished from Euconnus s. str. based on the antennal, pronotal and male genital structures. However, in other regions, described and undescribed species of Euconnus can be found that show intermediate features between these three subgenera. This problem is analyzed based on fourteen exemplary species that occur in the East Palaearctic region, mainly in Japan. It is concluded that there are intermediate forms between a trimerous antennal club, previously treated as the primary diagnostic feature of Psomophus, and a tetramerous club, typical of most species placed in Eupentarius and Euconnus s. str. The shape of the pronotum, the median pronotal antebasal pit, and the bifurcate aedeagal apex, thought to be typical of Eupentarius, were also found to vary among apparently closely related species. Consequently, Psomophus syn. n. and Eupentarius syn. n. are placed as junior synonyms of Euconnus s. str. The following species are redescribed or described: (1) Euconnus callidus group: E. chinensis Franz (China: Fujian), E. multiinsularis sp. n. (Japan: C & N Ryūkyū); (2) species sola E. rectitibia sp. n. (Japan: Honshū, Kyūshū); (3) Euconnus kirin group: E. kirin sp. n. (Japan: Honshū), E. yaimanus sp. n. (Japan: S Ryūkyū), E. uchinaanchu sp. n. (Japan: C Ryūkyū); (4) Euconnus pseudotrimerus group: E. pseudotrimerus sp. n. (Japan: Honshū), E. urauchianus sp. n. (Japan: S Ryūkyū); (5) Euconnus taiwanus group: E. taiwanus Franz (Taiwan and newly recorded from Japan: S Ryūkyū), E. fukiensis Franz (China: Fujian), E. bibaculatus sp. n. (Japan: S Ryūkyū), E. cryptoiriomotensis sp. n. (Japan: S Ryūkyū), E. oitaensis sp. n. (Japan: Kyūshū), and E. banana sp. n. (Japan: C Ryūkyū). A synonymic checklist of subgenera of Euconnus and a preliminary illustrated key to subgenera are given.